Herbicidal potential of phenolic and cyanogenic glycoside compounds isolated from Mediterranean plants - Ladhari, Afef; Romanucci, Valeria; De Marco, Anna; De Tommaso, Gaetano; Di Marino, Cinzia; Di Fabio, Giovanni; Zarrelli, Armando (Ecological Questions, 2018)
This study was conducted to test five phenolic and cyanogenic glycoside compounds for growth regulating activity on the germination and seedling growth of Portulaca oleracea L., Amaranthus retroflexus L., and Lactuca sativa L. at different concentrations. Overall, the tested compounds revealed growth-regulating activity in species-specific and concentration dependent manner. The most powerful effects were much pronounced on seedling growth rather than on germination. In fact, the compounds 1 (amygdalin) and 2 (salicylic acid) were the most phytotoxic on root growth of P. oleracea, and they caused, respectively, an inhibition of 55% and 85% at 10-6 M and 10-4 M. On the other hand, the lettuce seedling growth was more sensitive than weeds growth to the compounds 4 (3,4,5-trihydroxybenzoic acid) and 5 (7-hydroxycoumarin), which exhibited a moderate inhibition at the highest concentration. This selectivity and specificity of these active allelopathic compounds could be very useful for the development of new application of natural substances to control the aggressive weeds. Thus, our findings suggest that the integration of these compounds may maintain irrigation system and reduce the massive use of agrochemicals in agro-ecosystems.